V4641 Sgr: A candidate precessing microblazar - Gallo, E.; Plotkin, Richard; Jonker, P. (Oxford Academic, 2014)
The X-ray spectrum of the Galactic X-ray binary V4641 Sgr in outburst has been found to exhibit a remarkably broad emission feature above 4 keV, with inferred equivalent widths up to 2 keV. Such a feature was first detected during the X-ray flaring activity associated with the giant outburst that the source experienced in 1999 September. The extraordinarily large equivalent width line was then ascribed to reflection/reprocessing of fluorescent Fe emission within an extended optically thick outflow enshrouding the binary system as a result of a shortlived, super-Eddington accretion episode. Making use of new and archival X-ray observations, we show here that a similar feature persists over four orders of magnitude in luminosity, down to Eddington ratios as low as log (LX/LEdd)~-4.5, where the existence of an optically thick envelope appears at odds with any viable accretion flow model. Possible interpretations for this highly unusual X-ray spectrum include a blend of Doppler-shifted/boosted Fe lines from unresolved X-ray jets (a la SS433), or, the first Galactic analogue of a blazar spectrum, where the >4 keV emission would correspond to the onset of the inverse Compton hump. This either requires a low-inclination angle of the jet with respect to the line of sight, in agreement with the estimates for the 1999 superluminal jet (ijet <10°). The fast variability of the feature, combined with the high orbital axis inclination (60° <iorb <71°), argue for a rapidly precessing accretion flow around V4641 Sgr, possibly leading to a transient microblazar behaviour. © 2013 The Authors.